Instituting the symbolic debt (1993)
The rise of individualism has led us to believe that we, as human beings, are self-sufficient and are not bound by any constraints. Parental narcissism gives birth to omnipotence in children and the new generations, no longer in debt to an Absolute Referent, are not marked by the acceptance of death. Thus, death denied reappears not as a sacrifice but as holocaust.